The Flowering Integrator FT Regulates SEPALLATA3 and FRUITFULL Accumulation in Arabidopsis Leaves - Teper-Bamnolker, Paula (American Society of Plant Biologists, 2005)
The transition to flowering involves major changes in the shoot apical meristem and in the fate of existing leaf primordia. Transcripts of the Arabidopsis thaliana flowering-promoting gene FLOWERING LOCUS T (FT) are present in leaf tissue but can also promote flowering when artificially introduced into the meristem. FT may normally act in the leaf and/or the meristem, initiating or constituting a mobile flower-promoting signal. We studied FT-dependent events in the rosette leaf, some of which might precede or mimic events in the meristem and its primordia. We show FT-dependent transcript accumulation of the MADS box transcription factors FRUITFULL (FUL) and SEPALLATA3 (SEP3) in leaves. Abnormally high levels of FT further increase the expression of these genes, leading to morphological changes in the leaves. Loss of the flowering-time gene FD, as well as environmental conditions that delay flowering, reduce FT's effect on leaves via reduced activation of its targets. FUL, SEP3, and APETALA1 accumulation in the meristem is associated with and contributes to the transition to flowering. We propose that FT functions through partner-dependent transcriptional activation of these and as-yet-unknown genes and that this occurs at several sites. Organ fate may depend on both degree of activation and the developmental stage reached by the organ before activation occurs.